BUKMUK’s Marketing Puzzle - Putting the Pieces Together : A Case Study - Chaudhary, Karishma; Singh, Pragya; Pallavi (Indian Journal of Marketing, 2025)
Purpose : This case study explored the multifaceted marketing challenges encountered by a nascent entrepreneurial venture operating in a dynamic and resource-constrained environment. By examining the real-life experiences of Ms. Shefali, the founder of BUKMUK, the case aimed to facilitate critical thinking around strategic decision-making in marketing. The study aimed to provide learners with a practical context to apply core marketing concepts and frameworks, illuminating the nuanced dilemmas faced by early-stage entrepreneurs in aligning business vision with market realities. Methodology : The case study employed a qualitative, exploratory methodology grounded in primary and secondary data collection. Primary data was obtained through a series of in-depth, semi-structured interviews conducted with the protagonist, Ms. Shefali. In addition to original data, secondary sources like company websites, social media platforms, and other publicly accessible documents were also examined. Theoretical frameworks associated with customer segmentation, marketing strategy, and entrepreneurial marketing were utilized to guide the analysis and the creation of the related teaching note. This combined methodology guarantees that the case offers a comprehensive, evidence-based perspective on the marketing issues. Practical Implications : This case study offered actionable insights for early-stage entrepreneurs, marketing professionals, and educators by illustrating how marketing theory can be pragmatically applied to real-world business challenges. Originality : This case study was original in both its content and methodological approach. It was based on first-hand, primary data collected through a series of exclusive interviews with the protagonist, Ms. Shefali, the founder of BUKMUK.